RELEVANSI SYAHID MA'NAWI DENGAN PERISTIWA PANDEMIC COVID-19: STUDI MATAN PENDEKATAN MA'ANIL HADIS - Dede Mardiana; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to discuss the hadis syahid ma'nawi about infectious diseases of relevance to the situation of the Covid-19 pandemic. This research is a type of qualitative interpretation of matan (hadith text) using the method of interpreting the hadith (ma'anil hadith). The results and discussion of the study are syahid ma'nawi, in the theory and methodology of hadith science, about the hadis surrounding infectious diseases, which are spread in the hadith chapters, have opened a clear understanding in their relevance to the situation of the Covid-19 pandemic in this modern era. This study concludes that the hadis syahid ma'nawi about infectious diseases teaches relevant core values to be a formula for the Covid-19 pandemic opponents.